Refractive Index of 0.4 Molar Paramagnetic FeCl3 Solution in Absence and in Presence of Non Uniform Magnetic field - Rajendra Patankar, Pratik (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Using hollow glass prism, Spectrometer and monochromatic Sodium source as a light source refractive index of 0.4 Molar FeCl3 solution was obtained in absence and in presence of non-uniform magnetic field at room temperature. It was found that refractive index of 0.4 molar paramagnetic FeCl3 solution is lesser in presence of non-uniform magnetic field than in absence of magnetic field. When non uniform magnetic field is applied across FeCl3 solution its refractive index decreases due to torque and magnetic force acting on magnetic dipole of the solution. Such torque and force causes paramagnetic matter to move from area of weaker to stronger magnetic field to create non uniform density in medium. Using Fermat principle it was concluded that refractive index of medium in presence of non-uniform magnetic field decreases